2021
DOI: 10.3390/su132011271
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variation and Terrain Gradient Effect of Ecosystem Services in Heihe River Basin over the Past 20 Years

Abstract: With the advent of large-scale development, extreme imbalance in the ecology of the Heihe River Basin (HRB) has caused a series of ecological problems. In order to explore the spatiotemporal variation of ecosystem services (ESs) and to assess the characteristics of ESs under the terrain gradient effect (TGE), the three key ESs were quantified based on the InVEST model using five series of land-use data obtained from remote sensing images from 2000 to 2020 in this study. The terrain index was used to analyze th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Topography is an essential geographic parameter in habitats and a critical component of biological habitat composition, significantly impacting the distribution, reproduction, and habitat of species [47,49]. Numerous studies have shown that topographic features such as altitude, slope, and aspect significantly affect species' distribution patterns in local climatic environments by influencing the distribution of regional water and heat, material transfer, and conversion.…”
Section: Topographic Diversity Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Topography is an essential geographic parameter in habitats and a critical component of biological habitat composition, significantly impacting the distribution, reproduction, and habitat of species [47,49]. Numerous studies have shown that topographic features such as altitude, slope, and aspect significantly affect species' distribution patterns in local climatic environments by influencing the distribution of regional water and heat, material transfer, and conversion.…”
Section: Topographic Diversity Indexmentioning
confidence: 99%
“…Given that Haitan Island is the main island of Pingtan County, characterized by a dense population and rapid urbanization, this study identified urban land, rural residential land, primary and secondary roads, and farmland as threats due to their greater human disturbance. Relevant parameters were established based on the Invest model user guide and related literature [24,47,48] (see Tables 1 and 2).…”
mentioning
confidence: 99%
“…The ecohydrological processes related to climate and vegetation at different altitudes behave differently [20][21][22][23][24], resulting in changes in water yield along the altitudinal gradient. Currently, many scholars have introduced the effect of terrain differences to carry out related research, such as when Zhang introduced the Terrain Niche Index to analyze the impact of the terrain gradient on ecosystem services in the Heihe River Basin, and pointed out that there is a positive correlation between water yield and the Terrain Niche Index [25], but Ma et al pointed out that water yield was relatively low in the high topographic gradient zone, and there was a decreasing trend of water yield with an increasing elevation [26,27]. Apparently, there are regional variations in water yield with the altitude gradient, which are related to the climate, vegetation and land use types at different altitude gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Du et al [6], in their study titled "The Impact of Impervious Surface Expansion on Soil Organic Carbon: A Case Study of 0-300 cm Soil Layer in Guangzhou City", showed that impervious surface expansion leads to soil organic carbon (SOC) loss and that retrofitting residential areas with low-rise buildings can significantly reduce SOC loss compared to the urbanization of agricultural land. For a large-scale development, Zhang and Hu [7] analyzed the effect of topography on ES in their study titled "Spatial Variation and Terrain Gradient Effect of Ecosystem Services in Heihe River Basin over the Past 20 Years". They showed that terrain gradient effects have a significant impact on ESs in inland watersheds, providing a scientific basis for optimizing local ecological patterns.…”
mentioning
confidence: 99%